Comparison of Size Reduction Techniques in Spiral Antenna Design - Sag, Rabia Nur; Tuylu, Tolgahan; Tokan, Nurhan Turker (IEEE, 2023)
In this work, size reduction techniques of the spiral antenna are presented by comparing the size reduction performances over a 2-arm Archimedean spiral antenna. Size reduction techniques of adding a ring around the spiral, tapering the termination of the spiral arms, using meander line around the spiral, and terminating the spiral arm with resistive load are applied to obtain miniaturize the antenna. Simulation results of the size reduction techniques are compared with the basic specifications of having S-11 below -10 dB, axial ratio (AR) below 3 dB, and gain higher than 0 dBi at the lowest frequency of the band. The detailed analysis results of the techniques show that maximum size reduction of 21.32 percent is obtained in the antenna physical area by the tapered line termination technique.
Keywords: archimedean; meander line; resistive loading; ring; spiral antenna; tapered line; gap loading; size reduction; Engineering; Imaging Science & Photographic Technology